Pengaruh Metode Gerak dan Lagu Terhadap Kecerdasan Kinestetik Anak Usia5-6 Tahun di TK Negeri Kartini Desa Duano Kecamatan Suwawa TengahKabupaten Bone Bolango - Leysa Tagele; Sri Wahyuningsi Laiya; Nunung Suryana Jamin (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This article discusses the impact of the Movement and Song Method on the Kinesthetic Intelligence of 4-5 Year old Children at TK State Kartini Kindergarten, Duano Village, Suwawa Tengah District, Bone Bolango Regency. The study aims to determine how the movement and song method impacts the kinesthetic intelligence of 5-6 year old children. This quantitative research employed an experimental method. The research design used was a one-group pretest-posttest design with data collection techniques, including observation and tests. The subjects were 5-6 year old children, with a sample size of 15 children. Based on the t-test analysis (paired sample test), the results showed that tcount was greater than ttable (14.701 > 2.160) and the sig (2-tailed) = 0.000 < 0.05. Therefore, Ha was accepted, and the HO was rejected. It can be concluded that the movement and song method significantly impacts the kinesthetic intelligence of 4-5 year old children at TK State Kartini Kindergarten, Duano Village, Suwawa Tengah District, Bone Bolango Regency.